Design of Low Power Cam Memory Cell for the Next Generation Network Processors - Muralidharan, K.; Maheswari, S. Uma (IRO Journal on Sustainable Wireless Systems, 2021)
In the modern world, high performance embedded applications in the field of multimedia, networking, and imaging are increasing day by day. These applications require high performance and more complex out-of-order superscalar processor. These complex dynamic instructions scheduling superscalar processors need higher levels of on-chip integration designs which are often associated with power dissipation. These out-of-order superscalar processors achieve higher performance compared to other processors by simultaneous fetching, decoding and execution for multiple instructions in out-of-order that are used in the next generation network processors. The main data path resources of the processor use CAM+RAM structure which is the major power consuming unit in the overall out-of-order processor design. The proposed new design of CAM+RAM with power-gating technique reduces the overall average power consumption compared to the conventional design without any significant impact on their performance.
Keywords: Static Power; dynamic power; CAM; SRAM